DETERMINASI KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN SEKTOR KEUANGAN DI INDONESIA - Putu Novia Hapsari Ardianti; Putri, Cokorda Istri Agung Evita Nindia (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2025)
This study aims to examine the effect of company size, liquidity, profitability, and institutional ownership on the timeliness of financial reporting, as well as the role of the risk monitoring committee as a moderating variable. The study was conducted on financial sector companies listed on the Indonesia Stock Exchange during the period 2021 to 2023, yielding a sample of 25 companies with a total of 75 observations. The analysis method used was logistic regression. The results indicate that liquidity, profitability, and institutional ownership have a positive effect on the timeliness of financial reporting, while company size does not influence timeliness. The results also indicate that the risk monitoring committee is unable to moderate the relationship between the four independent variables and the timeliness of financial reporting. This finding suggests that the existence of a risk monitoring committee does not play a role in improving reporting timeliness. This study contributes to the development of financial reporting literature and can be used as input for companies and regulators in their efforts to improve corporate responsibility and governance